A Prospective Determination of the Incidence of Perceived Inappropriate Care in Critically Ill Patients - Rohit K Singal; Robert Sibbald; Brenda Morgan; Mel Quinlan; Neil Parry; Michael Radford; Claudio M Martin (Canadian Respiratory Journal)
BACKGROUND: Health care providers’ perceptions regarding appropriateness in end-of-life treatments have been widely studied. While nurses and physicians believe that rationing and other cost-related practices sometimes occur in the intensive care unit (ICU), they allege that treatment is often excessive.